Influencing Factors for Employability of University Graduates in the Tourism Industry - OMARKHANOVA, Zhibek; BESPAEV, Murat; MUKHAMBETOVA, Zamira; MUSSINA, Raushan; KUNAFINA, Gulzhan; RYSMAGANBETOVA, Anargul (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.v13.8(64).20, 2022)
The employability of graduates is a vital aspect for both higher education institutions and the graduates themselves. In order to study the factors influencing the employability of graduates, attention should be paid to the human factor in the educational environment and its impact on the development of the tourism industry. This article aims to description the factors of competitiveness of university graduates in the labor market and their influences on the tourism industry. Background research is devoted to the study of various aspects of social competition and competitiveness, allowing to the authors highlight the factors that indicate the need of a university graduate to be competitive induced by the internal need for competitiveness of graduates in the labor market of tourism.